The Influence of Introduction to the School Field, Family Environment, and Peers on Career Choices to Become Teachers in Students: Pengaruh Pengenalan Lapangan Persekolahan (PLP), Lingkungan Keluarga Dan Teman Sebaya Terhadap Pilihan Karir Menjadi Guru Pada Mahasiswa - Salma Fina; Reni Andriani (Yayasan Siti Widhatul Faeha, 2025)
The declining interest of education students in pursuing a teaching career raises concerns about the future availability of qualified teachers, leading to the need to examine the factors influencing students’ career choices. This study aims to analyze the extent to which perceptions of the teaching profession, the family environment, and experiences in the School Field Introduction (SFI) affect students’ interest in becoming teachers. The research involved 82 students of the Economic Education Program selected through proportional random sampling. Data were analyzed using instrument testing, classical assumption testing, and multiple linear regression analysis. The results show that perceptions of the teaching profession, the family environment, and SFI experiences simultaneously have a positive and significant effect on students’ interest in becoming teachers. Partially, perceptions of the teaching profession and SFI experiences showed significant positive effects, while the family environment did not. The study concludes that strengthening positive perceptions and providing meaningful field experiences are key to increasing students’ interest in the teaching profession. These findings imply that universities and policymakers should design programs that enhance students’ professional perceptions, increase family support, and optimize PLP implementation to encourage more competent and motivated prospective teachers.